Influential Factors, Treatment and Prognosis of Autoimmune Encephalitis Patients With Poor Response to Short-Term First-Line Treatment - Liu, Fei; Zhang, Bingbing; Huang, Teng; Wang, Baojie; Wang, Chunjuan; Hao, Maolin; Guo, Shougang (Frontiers in Neurology, 2022)
Objective: This study was performed to assess the potential factors for poor short-term first-line treatment response, the appropriate further treatment options, and the prognosis in patients with autoimmune encephalitis (AE). Methods: This retrospective study consisted of 135 AE patients. According to their short-term first-line treatment response, patients were divided into response group and non-response group. The demographics, clinical characteristics, main accessory examinations, immunotherapy, and outcomes of patients were compared between the two groups. Univariate and multivariate logistic regression model were used to analyze whether non-responders have poor long-term outcomes. Further treatment and prognosis of non-responders were also analyzed. Results: Of the 128 patients who were treated with first-line immunotherapy, 59 (46.1%) were non-responders. Patients in the non-response group had more symptoms, and exhibited a higher proportion of mental behavior disorder, central hypoventilation, and autonomic nervous dysfunction. The mRS scores, NLR levels were significantly higher and albumin, HDL-C, apoA levels were significantly lower in non-response group (p＜0.05, all). Multivariate logistic regression analysis showed that number of clinical symptoms, mental behavior disorder, central hypoventilation, maximum mRS score and albumin level were independently associated with non-response to short-term first-line treatment. Non-responders had poor long-term outcomes compared with the responders at all times of followed-up (p＜0.05, all). In multivariable analysis, initial first-line treatment response was independently associated with the long-term prognosis, both at 12-month (OR, 4.74, 95% CI, 1.44-15.59, p=0.010) and 24-month follow-up (OR, 8.81, 95% CI, 1.65–47.16; P=0.011). Among the non-responders, a higher improvement of mRS scores was observed in those received second-line treatment than those who had no further treatment or repetition of first-line immunotherapy in the follow-up. However, the rate of good outcome and median mRS scores were not significant different among the three groups. Conclusions: Disease severity, clinical features, anti-NMDAR subtypes, antibody titers, NLR, albumin, HDL-C and apoA levels were all associated with nonresponse to short-term first-line treatment. The short-term first-line treatment response is a valuable predictor of long-term outcome in patients with AE. Second-line immunotherapy maybe a more aggressive treatment option for patients who failed short-term first-line immunotherapy.